Age-specific differences in wing pointedness and wing length of European Turtle Doves Streptopelia turtur migrating through the eastern flyway. Issue 2 (2nd July 2020) - Thoma, Charalambos T.; Makridou, Konstantina N.; Bakaloudis, Dimitrios E.; Vlachos, Christos G.
ABSTRACT: Migration plays a significant part in shaping wing morphology in avian taxa. Differences in wing shape and size have been found to vary with regard to age and sex, as well as between different populations. Here, we examine age-related variation in the wing morphology of the European Turtle Dove Streptopelia turtur migrating through the eastern flyway. Wing morphology was examined by means of a size-constrained components analysis (SCCA) of standardised primary-feather lengths of 112 individuals killed by hunters. Our results showed that juvenile individuals had shorter and more pointed wings than adults, which is consistent with the pattern observed in individuals migrating through the western flyway. We conclude that in juveniles, the selection force of migration is perhaps stronger than selection of an anti-predator adaptation. Moreover, age-related variation in Turtle Dove wing morphology may influence juvenile survival, as well as migration timing, and both effects should be considered in future studies.